2000
DOI: 10.1016/s0887-6177(99)00002-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance Curve Classification of Invalid Responding on the Validity Indicator Profile

Abstract: The purpose of this article is to provide evidence for the validity of performance curve classification on the nonverbal subtest of the Validity Indicator Profile (VIP-NV). A four-fold classification scheme of performance on cognitive testing is proposed. This scheme combines effort and motivation to generate four response classifications: compliant, careless, irrelevant, and malingering. Data are presented across six studies from cognitive and personality testing for 737 male pretrial criminal defendants. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Thus, like the TOMM, where extremely low scores should result in greater confidence about the likelihood of malingering, a Suppressed response style appears to provide far stronger evidence of malingering than other Invalid response styles (Irrelevant or Inconsistent). This conclusion, which is similar to one offered by Frederick, Crosby, and Wynkoop (2000), may be even more important in cases where an individual is presenting with psychotic symptoms.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Thus, like the TOMM, where extremely low scores should result in greater confidence about the likelihood of malingering, a Suppressed response style appears to provide far stronger evidence of malingering than other Invalid response styles (Irrelevant or Inconsistent). This conclusion, which is similar to one offered by Frederick, Crosby, and Wynkoop (2000), may be even more important in cases where an individual is presenting with psychotic symptoms.…”
Section: Discussionsupporting
confidence: 74%
“…Frederick, Crosby, and Wynkoop (2000) administered the Non-Verbal subtest of the VIP to a sample of forensic psychiatric patients. They compared 120 forensic psychiatric patients (80 of whom were diagnosed with a psychotic disorder) to 120 non-mentally ill inmates.…”
mentioning
confidence: 99%
“…The TOMM and CVLT-II appear to offer non-redundant information in this regard. Other viable choices that have become available in recent years for this purpose include the Word Memory Test [41,42], the Computerized Assessment of Response Bias [43,44], the Validity Indicator Profile [45,46] and the Victoria Symptom Validity Test [47,48]. Recent research has suggested that some of these tests may be more sensitive to invalid neuropsychological test performance than the TOMM, although their false positive rates are not entirely clear and comparisons with the CVLT-II have, to the authors' knowledge, not yet been performed [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The VIP has been validated in a variety of samples (e.g., brain injury, suspected and "coached" malingerers; Frederick, 2002;Frederick, 2003;Frederick, Crosby, & Wynkoop, 2000) and has good sensitivity (Nonverbal: 74%, Verbal: 67%) and specificity (Nonverbal: 86%, Verbal: 83%)-better than other measures of malingering that have previously been used in CFS research (i.e., Portland Digit Recognition Test, Rey 15-Item Memory Test, Dot Counting Test; .…”
Section: Methodsmentioning
confidence: 99%